Mrs Optimalisasi Hafalan Al-Qur’an Siswa Sd Muhammadiyah Ponorogo Melalui Implementasi Talaqqi Metode Ummi - Femi Astika Candra Chairani; Rido Kurnianto; Syamsul Arifin; Edi Priyatno; Moch. Charis Hidayat (Jurnal Manajemen Pendidikan, 2025)
BackgroundThe study is motivated by the observation that many students enrolled in the Tahfidz program still struggle to meet the standards of Al-Qur’an recitation and Tajwid knowledge. PurposeThis research aims to examine the implementation of the Ummi method through Talaqqi in enhancing the reading and memorization skills of Tahfidz class students at Muhammadiyah Elementary School of Ponorogo. Design/method/approachThis study employs a qualitative case study design, with data collected through interviews, document analysis, participant observation, and documentation. The research focuses on the process of planning, implementation, and evaluation of learning, as outlined in the teachers’ lesson plans (RPP) and executed through seven teaching stages. ResultsFindings indicate that students not only memorize the Qur’an but also improve their recitation quality and responsibility through various activities. The results show that the Ummi method significantly enhances students’ memorization outcomes, helping them meet the school’s Qur’an memorization targets, recite with proper Tajwid and pronunciation, and develop consistent responsibility in completing assignments. Contribution/valueThe study demonstrates that the Ummi method through Talaqqi is an effective strategy for improving both the memorization and reading skills of Tahfidz students at Muhammadiyah Elementary School of Ponorogo.